By definition of multiplication of powers of the same base we have to put the same base and add the exponents, then, we can rewrite the expression as:
![(2 ^ {\frac {1} {2} + \frac {3} {4}}) ^ 2 =\\(2 ^ {\frac {4 + 6} {8}}) ^ 2 =\\(2 ^ {\frac {10} {8}}) ^ 2 =\\(2 ^ {\frac {5} {4}}) ^ 2 =](https://img.qammunity.org/2020/formulas/mathematics/middle-school/i52k0fw44u8pticubqwuyneozc0fnzc0np.png)
By definition of power properties we have to:
![(a ^ n) ^ m = a ^ {n * m}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/nmupao2dxfydti0o42it0xbi1lds49kdtb.png)
So, we have:
![2 ^ {\frac {10} {4}} =\\2 ^ {\frac {5} {2}} =](https://img.qammunity.org/2020/formulas/mathematics/middle-school/wfovbh341bc1qn0kfhapc3fgzranqarghn.png)
By definition of properties of powers and roots we have:
![\sqrt [n] {a ^ m} = a ^ {\frac {m} {n}}](https://img.qammunity.org/2020/formulas/mathematics/high-school/suo6ai2uezolc3t7f2f9e9h1lijquf271f.png)
So, the expression is equivalent to:
![2 ^ {\frac {5} {2}} = \sqrt {2 ^ 5}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/reo4kfiolsevjukaxslu98z80tamlhgznz.png)
ANswer:
Option B